Hydroponic Melon Cultivation Based on The Dutch Bucket System as A Solution to Improve The Family Economy After Natural Disasters in Sigi District - Al Riski, Mohamad; Laapo, Alimudin; Yusuf, Ramal (Unram Journal of Community Service, 2024)
The earthquake and liquefaction disaster in 2018 and the Covid-19 outbreak had an impact on the economic decline of the people in Sigi Regency, resulting in a low Family Economic Resilience Index. This study aims to design a model for empowering women's groups in Sigi Regency, in order to improve the family economy by providing education regarding melon cultivation (Cucumis melo L.) which is supported by the application of the Dutch bucket hydroponic system as a business opportunity. The target and location of the study is the Family Welfare Empowerment Group (PKK) in Soulowe Village, most of whom work as housewives. The analytical method used in designing the economic empowerment of PKK families is Participatory Rural Appraisal (PRA) analysis. The stages of participatory implementation include assessing the needs of community groups through filling out questionnaires, outreach, training, assistance with maintenance, harvest and post-harvest, and marketing. The results of the program implemented are the availability of a hydroponic installation used for the melon cultivation process, a partner guidebook that can assist partners in carrying out the cultivation process independently, quality organic melon harvests, a marketing partnership for cultivated products with fruit shops and support from village government to develop existing programs. So, this program can continue to be sustainable and become the right solution to help improve the economy of families in Soulowe Village.